Relationships between anxiety, depression and wound healing outcomes in adults: A systematic review and meta-analysis. - Fiona O'Donovan; Lora Capobianco; Joseph Taylor-Bennett; Adrian Wells (PLoS ONE)
Objectives To examine whether there is a relationship between anxiety and/or depression and wound healing. Design Systematic review and meta-analysis. Data sources Searches were conducted on PsycINFO, MEDLINE, EMBASE, CINAHL and Web of Science on the 06-March-2023. Methods Eligible studies explored the effects of anxiety and/or depression on wound healing in adults. Healing outcomes included time to heal and complication rates. Anxiety and depression outcomes were considered separately. Results Fifty-five studies were included in the narrative synthesis (26,612,809 participants), and 26 studies in the meta-analysis. Studies utilised a range of observational and experimental designs. Wounds included in the review were: surgical, ulcer, burn and experimental wounds. The narrative synthesis gave mixed results, with some studies noting positive associations between increased anxiety or depression and wound healing, while others did not find an association. Results from the meta-analysis found no significant effect of anxiety on wound healing outcomes. However, depression was associated with significantly higher odds of delayed wound healing, OR = 2.10, [1.02, 4.33]; higher risk of wound complications, RR = 1.30, [1.11, 1.53] and increased risk of wound infection RR = 1.25, [1.09, 1.44]. Conclusion These findings suggest depression negatively impacts wound healing. There is less evidence for an association with anxiety, but this may be due to less research in this area. Future studies should explore the mechanism of associations between depression and wound healing to inform clinical interventions.